Fertility in Sub-Saharan African countries with consideration to health and poverty - Yongil Jeon; Sang-Young Rhyu; Michael P. Shields (Institute for the Study of Labor (IZA), 2008)
Fertility has begun to fall in Sub-Saharan Africa but it remains high on average and particularly for a few countries. This paper examines African fertility using a panel data set of 47 Sub-Saharan countries between 1962 and 2003. Fixed and random country effect estimates are made in models where the explanatory variables are suggested by the theory of the demographic transition as modified by Caldwell. Special attention is paid to the economic status of women, urbanization, the poverty level, and the health of the population including total health expenditures and the prevalence of HIV/AIDS. The results support Caldwells hypothesis and are generally supportive of hypothesis that a fertility transition is occurring. HIV/AIDS is found to have a negative impact on fertility.
urn:nbn:de:101:1-2008060976
Keywords: J13; 330; Fertility; infant mortality; Africa; poverty; health; Fruchtbarkeit; Demographischer Übergang; Kindersterblichkeit; Frauenerwerbstätigkeit; Gesundheit; Urbanisierung; Armut; Afrika südlich der Sahara